2016
DOI: 10.1002/pbc.25945
|View full text |Cite
|
Sign up to set email alerts
|

Conditional Survival and Predictors of Late Death in Patients With Ewing Sarcoma

Abstract: The majority of late deaths in 5-year survivors are due to EWS. Black race, age ≥18 at diagnosis, male sex, and axial/pelvic primary site (but not stage at diagnosis) are independently associated with increased risk of late death.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
18
0
2

Year Published

2017
2017
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 20 publications
1
18
0
2
Order By: Relevance
“…that most cases of Ewing's sarcoma not surprisingly emerged before the second decade of life, and that younger patients were likely to have a better prognosis. [15][16][17] Regarding the reasons for this phenomenon, Lee et al 18 and Grevener et al 16 found that fewer cases among adult patients were treated with chemotherapy. Moreover, elderly patients were more likely to have several comorbidities, including diabetes mellitus hypertension or secondary cancers, which made the situation much more complex.…”
Section: Discussionmentioning
confidence: 99%
“…that most cases of Ewing's sarcoma not surprisingly emerged before the second decade of life, and that younger patients were likely to have a better prognosis. [15][16][17] Regarding the reasons for this phenomenon, Lee et al 18 and Grevener et al 16 found that fewer cases among adult patients were treated with chemotherapy. Moreover, elderly patients were more likely to have several comorbidities, including diabetes mellitus hypertension or secondary cancers, which made the situation much more complex.…”
Section: Discussionmentioning
confidence: 99%
“…Our study included several local therapy options (e.g., PT with or without surgery) and did not focus on either radical PT or PORT. Due to the limited number of events, we could not perform multivariate analyses to control for potential confounding factors in our examination of outcome endpoints . Detailed data on surgical margins and the pathologic response to chemotherapy were not routinely available for the operated patients and, thus, were not included in the analysis.…”
Section: Discussionmentioning
confidence: 99%
“…Young age with various age cutoffs has been identified as a favorable prognostic factor in multiple series. 25,31,[38][39][40] Recently, Karski et al…”
Section: Discussionmentioning
confidence: 99%
“…Conditional survival (CS) measures the probability that a patient will survive for an additional number of years having already survived for a certain number of years. Thus, CS estimation presents a more dynamic and accurate measure of prognosis for patients who had already survived for some time beyond their diagnosis . Many previously published data revealed distinct patterns of CS that vary substantially according to diagnoses such as colon cancer, hepatocellular carcinoma, ovarian cancer, gall bladder cancer, and gastric cancer .…”
Section: Introductionmentioning
confidence: 99%
“…Thus, CS estimation presents a more dynamic and accurate measure of prognosis for patients who had already survived for some time beyond their diagnosis. [4][5][6][7][8][9][10] Many previously published data revealed distinct patterns of CS that vary substantially according to diagnoses such as colon cancer, hepatocellular carcinoma, ovarian cancer, gall bladder cancer, and gastric cancer. [7][8][9][10] As far as we know, no previous study has attempted to evaluate the CS of extremity STS patients.…”
mentioning
confidence: 99%